Effect of brine type and pH on the interfacial tension behavior of carbonated brine/crude oil. Issue 8 (14th June 2021) - Zaker, Saeed; Parvizi, Roohollah; Ghaseminejad, Ebrahim; Moradi, Amin
Abstract: Although carbon dioxide (CO2 ) injection is an efficient tool to enhance the oil recovery, deposition of asphaltenes, extensive gas consumption, rapid breakthrough of CO2, etc. faced it with serious challenges. As a solution for these disadvantages, the injection of dissolved CO2 in water instead of direct CO2 injection is proposed during the past decade. Respect to this fact, in the current investigation, the dynamic interfacial tension (IFT) values of carbonated brines/acidic crude oil are measured to examine synergetic or antagonistic effect of CO2 and aqueous solution consisted of sulfate anions i.e. 15000 ppm of MgSO4 and Na2 SO4 in a wide range of temperatures (30–80 °C) and pressures (500–4000 psi). The sulfate anion based salts are considered in the current investigation wince it has been well established that sulfate anion can introduce more profound effects on the dynamic IFT variation. Considering the obtained results and comparing them with the previously published studies, one can conclude that the variation of IFT of crude oil/carbonated brine as a function of temperature and pressure is completely different compared to IFT of crude oil/brine due to lower pH resulted regarding the dissolution of CO2 in aqueous phase, dominant effect of CO2 at higher pressures and more diffusivity of CO2 at higher temperatures. Graphical Abstract: Dynamic IFT of Na2 SO4 brine/crude oil at pressure of P  = 500 psi